A simplified approach to high strain rate effects in cold deformation of polycrystalline FCC metals: Constitutive formulation and model calibration. (July 2016) - dos Santos, Tiago; Rosa, Pedro A.R.; Maghous, Samir; Rossi, Rodrigo
Abstract: This work describes a macroscopic finite elastic–viscoplastic constitutive formulation that accounts for the individual contributions of strain hardening, strain rate induced hardening and viscous behavior in cold deformation of polycrystalline FCC metals. The constitutive modeling follows a Perzyna -type formulation within the thermodynamics with internal variables framework. The approach introduces a single phenomenological internal variable defining an effective microstructural feature, which comprises strain hardening contributions related to large strain processes. Internal variable evolution is based on physical considerations and gives rise to a modified Voce hardening law, which allows for predicting both the strain rate history effects and the linear hardening at large strains. Instantaneous rate-sensitivity is accounted for by a phenomenological overstress function. Material parameters are adjusted using experimental data available in literature for annealed high purity copper. Comparisons with experimental results and other viscoplastic models have demonstrated the model aptitude to properly predict high strain rate effects in cold deformation of polycrystalline FCC metals. Highlights: A simple effective constitutive proposal is presented to model viscoplastic metals. Model calibration is performed in subsequent steps in a wide strain rate range. Proposed model captures the sudden raising of flow stress at high strain rates. Model predicts strain rate history effects and linear hardening at large strains.